2008
DOI: 10.1007/s11103-008-9343-3
|View full text |Cite
|
Sign up to set email alerts
|

Barley (Hordeum vulgare L.) inositol monophosphatase: gene structure and enzyme characteristics

Abstract: The cellular myo-inositol (Ins) pool is important to many metabolic and signaling pathways in plants. Ins monophosphatase (IMPase; EC 3.1.3.25) activity is essential for the de novo synthesis of myo-Inositol (Ins), and for recycling of Ins in Ins(1,4,5)P3. However, proteins encoded by at least one family of IMP genes also have L-galactose-1-P phosphatase activity important to ascorbic acid synthesis, indicating a bifunctionality that links these two branches of carbon metabolism. As part of research into the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…The apparent V max for VTC4 with D-Ins 3-P was 4.0 units and that for L-Gal 1-P was 5.4 units. In general, these kinetic parameters are comparable to those found for the Lilium IMP (K m of 78 mM for D-Ins 3-P; Loewus and Loewus, 1982) and kiwifruit VTC4 (K m of 150 mM for L-Gal 1-P and 330 mM for D-Ins 3-P; Laing et al, 2004; Table II), yet they differ from the previously reported values for the Synechocystis (Patra et al, 2007) and barley (Hordeum vulgare) enzymes (Fu et al, 2008), which have lower K m values (Table II). Furthermore, the ratio of V max to K m provides one measure of discriminating substrate preference, and we found that there is a 1.7-fold difference in the ratios, indicating a small difference between L-Gal 1-P and D-Ins 3-P (Table II).…”
Section: Expression Of Recombinant Atvtc4 Proteinsupporting
confidence: 79%
“…The apparent V max for VTC4 with D-Ins 3-P was 4.0 units and that for L-Gal 1-P was 5.4 units. In general, these kinetic parameters are comparable to those found for the Lilium IMP (K m of 78 mM for D-Ins 3-P; Loewus and Loewus, 1982) and kiwifruit VTC4 (K m of 150 mM for L-Gal 1-P and 330 mM for D-Ins 3-P; Laing et al, 2004; Table II), yet they differ from the previously reported values for the Synechocystis (Patra et al, 2007) and barley (Hordeum vulgare) enzymes (Fu et al, 2008), which have lower K m values (Table II). Furthermore, the ratio of V max to K m provides one measure of discriminating substrate preference, and we found that there is a 1.7-fold difference in the ratios, indicating a small difference between L-Gal 1-P and D-Ins 3-P (Table II).…”
Section: Expression Of Recombinant Atvtc4 Proteinsupporting
confidence: 79%
“…The enzyme activity of this gene is essential for the de novo synthesis of myo-Inositol (Ins) and for the recycling of Ins into Ins (1,4,5)P 3 . This enzyme is a potential regulatory point for all pathways that utilize free Ins (Fu et al 2008). Glyma12g23920 and Glyma12g29790 are both members of the Triose-phosphate Transporter family, which is in the P storage and homeostasis pathways and mediates the transport of Pi between the cytosol and the stroma of the chloroplast (Flügge et al 1989(Flügge et al , 1999Raboy et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In many plant species, MIPS1, MIPS2, and MIPS3 encode myo-inositol 3-phosphate synthase, which catalyzes the conversion of D-glucose 6-phosphate to myo-inositol 3-phosphate in the de novo myo-inositol synthesis pathway (Abid et al 2009), and IMP catalyzes the last step of the conversion of glucose 6-phosphate to myo-inositol in tomato (Gillaspy et al 1995;Styer et al 2004), barley (Fu et al 2008), soybean (Islas-Flores and Villanueva 2007), rice (Suzuki et al 2007), and kiwifruit (Laing et al 2004). RNAi suppression of MIPS activity in potato (Solanum tuberosum) results in a variety of morphological changes (Keller et al 1998;Abid et al 2009).…”
Section: Introductionmentioning
confidence: 99%